PARENT-TRAINING TO SUPPORT PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDERS - Zorzi, Simone; Marzano, Gilberto (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Social inclusion necessitates educational efforts to be made to address everyday problems and difficulties. Researchers and practitioners widely emphasize the importance of training parents of children with special needs. Parents of children with Autism Spectrum Disorder have been successfully taught to improve their parent-child relationship, increase communication skills, and decrease inappropriate behaviors, as well as to reduce their psychological distress. This paper presents the results of a survey carried out within the two-year project EXEC (Extending Social Educators Competences) supported by the European Union.